A Propitious Approach towards Independent Directors in Malaysian Firms’ Board Committee - Michael, Tinggi; Abu Hassan, Md. Isa; Shaharudin, Jakpar (Canadian Center of Science and Education, 2015)
Independent directors at board committee have never taken a center stage, until when the world economy faced a global financial crisis stretching from the late 1990s to the late 2000s. Corporate governance ultimately calls for more controls and checks to be exercised at the board and committee level. Monitoring by independent directors of the top level management, is now viewed with more propitiation, complementing existing auditing activities, nominating and evaluating compensation to executive directors. The propitious approach is being interpreted as accepting independent directors favorably by increasing their representation at the board room and committee, which may be translated towards profit generation. A panel white standard error from an estimated 30 percent of the total Malaysian firms for period of 10 years suggests that nomination and remuneration committee gear the company towards generating profit.